The Impact of Community Nutrition Workers on Reducing Malnutrition in Pregnant Lactating Women of Tharparkar - Malhi, Parkash; Ahmed, Tanveer; Shaikh, Qamar; Baloch, Noor; Azeem, Kehkashan; Ali, Nazia Aftab (Indus Journal of Bioscience Research, 2025)
Background: Malnutrition is more prevalent in Pakistan. Objective: To assess the role of community nutrition workers in reducing malnutrition among pregnant lactating women of district Tharparkar. Methodology: A cross-sectional study was conducted among 305 pregnant and lactating women selected in the District Tharparkar. The data was analyzed by using SPSS version 25. The performance indicators of community nutrition workers and malnutrition status were described using mean, median, standard deviation, and IQR for quantitative variables, frequencies, and percentages for categorical data. The association between categories of MUAC and performance indicators (Home visits, IYCF sessions, and Sessions) of community health workers was assessed by applying the chi-square test. A P-value of 0.05 was considered significant. Results: The study's results revealed that approximately 305 pregnant lactating women were selected with a mean of 4.99 ± 2.395 and 85.9% of women belonged to the age group above 30 years. Hence the pregnant lactating women's nutrition status was based on MUAC at the time of screening and exit. At the time of screening, out of 305 PLW, 218(71.5%) were screened with MUAC of > 21 cm and identified as normal, 87(28.5%) were screened with MUAC of <21 cm and identified as malnourished pregnant lactating women. Conclusion: The study concluded that a local community-based worker selected by community participation can elevate the nutritional status of pregnant and lactating women in the district of Tharparkar.